Getting the cues of elder abuse: an identification through dependency and modernization. Issue 3 (27th April 2020) - Bajpai, Naval; Kulshreshtha, Kushagra; Dubey, Prince; Sharma, Gunjan
Abstract : Purpose: In the present era of modernization, the social group members interact with each other with selfish and unselfish intents. However, the unselfish means and ends build a long term relationship among people. On the other hand, selfish ends bud out unethical means such as abuses, violence and fights. The situation becomes tough when the same becomes evident among the family relationship and as a consequence the elderly are being treated unfairly. Out of such cases, some are reported and the majority of them remain unreported, which eventually becomes the cause of concern for the social welfare agencies. Thus, this paper aims to examine the elder abuse (EA) tendency in metro, non-metro and religious cities. Design/methodology/approach: For this study, a mixed-method approach is used to develop survey instruments, validate findings using qualitative and quantitative data sources for better generalization of results. The present study explored and confirmed the related factors using exploratory factor analysis and confirmatory factor analysis for the establishment of a valid scale of EA. Further, the difference of perceptions among the elders for abuse across the metro, non-metro and religious cities was statistically checked using the ANOVA and post hoc techniques. Findings: The present study identified the traces of EA and created a comprehensive understanding of it. The present study manifests the prevailing practices of EA in society by discussing the demerits of dependency and modernization. Moreover, the present study assesses the pervasiveness and the repercussion of dependency and the impact of modernization on EA followed by a discussion on how the victim elders may handle the situation. In the present study, a scale is developed to identify EA because of the dependency of the elderly and the modernization of society. Originality/value: Some exclaiming thoughts such as the dependency of elders elevate the chances of EA on one side, while modernization of society hampers the social/family bonding leading to EA. The inconsistent development across the region has created modernization as a significant factor for EA. The level and depth of modernization across locations such as metro, non-metro and religious cities are the cause for varying degrees of EA. Based on the literature review, the present study has sensed the presence of EA in society at large by developing a scale for the aforesaid purpose.